Relationship between speech parameters and individual psychological peculiarities - Ignatova, Natalija (Psichologija, 1999)
This thesis studies the rapport between the psychological and physiological aspects of an individual and his/her speech characteristics. For the purpose of creating an express-test to diagnose by the person’s speech behaviour a comparative analysis of speech, psychological, physiological and psycho-physiological parameters was undertaken. 25 people (heads of different branches of an enterprise aged 30 to 60) took part in the research. A number of various methods were applied to analyse each group of parameters. As a result some meaningful distinctions between the male and female group’s speech activity organization were defined. The connections between speech and individual psychological peculiarities were found in our research. The further research may bring about some reliable criteria to diagnose different characteristics of a person by his speech behaviour.